Life on Earth : A Natural History - Attenborough, David (London British Broadcasting Corporation, 1979)
A history of the natural world, of the evolution of life on this planet and the many different plants, animals and ecosystems which exist and have existed on land and sea.
Include Color Illustration and Index
Keywords: Zoology -- Evolution (Biology) -- Evolution